Performance degradation and component deterioration degree estimation for a turboshaft engine [Chinese language] - Huang, Kai-Ming; Li, Yiguang; Zhang, Wei; Feng, Xing; Cai, Jiang-bing (Zhongguo Hangkong Xuehui,Chinese Society of Aeronautics and Astronautics, 2015)
To monitor the performance and health conditions of a turboshaft engine during an endurance test, an engine mathematical model was set up and adapted to its real performance by adjusting component maps using a multiple-point performance adaption method. Gas path diagnostic analysis of the engine based on a non-linear gas path analysis (GPA) methodology was performed. In combination with field experiences, evaluation of the engine gas path component deterioration during an engine endurance test was carried out. The results indicated that the engine performance deviation and component deterioration varied over time. During initial phase of the test, the performance of the compressor and the compressor turbine deviated most rapidly then stabilized afterwards. As for the power turbine, the health was almost unchanged during the entire endurance test. The validation and experience of the GPA diagnostic technique prove that the technology can be applied into engine performance and health check for the evaluation of health of the turboshaft engine in its future service
Keywords: deterioration degree estimation; gas path analysis; performance degradation; component maps; turboshaft engine